Epithelioid haemangioma (angiolymphoid hyperplasia with eosinophilia subtype) involving the vermillion border of the lower lip. (5th February 2021) - Robinson, Liam; Lebaka, Chidinyane S.; van Heerden, Willie F. P.
Abstract: Epithelioid vascular tumours include benign epithelioid haemangioma (EH) and epithelioid angiomatous nodule, low‐grade malignant epithelioid haemangioendothelioma and high‐grade epithelioid angiosarcoma. These tumours share epithelioid cell morphologies and intracytoplasmic vacuoles, with distinction based on differing architectural and nuclear features. This report highlights a case of EH, angiolymphoid hyperplasia with eosinophilia subtype, involving the vermillion border of the lower lip in an elderly female patient. The clinical and histological features, differential diagnosis, aetiopathogenesis, molecular basis and treatment options are discussed as part of a comprehensive review of this rare entity.